Analysis of Different Treatment Approaches to Prevent Alveolar Osteitis: Treatment to Prevent Alveolar Osteitis - Sadiq, Muhammad Shairaz; Noor , Maria; Ishaq, Yaser; Saeed, Tooba; Syed, Amna Javed; Siddique, Sobia (Pakistan Journal of Health Sciences, 2024)
Alveolar Osteitis (AO) is a complication that can arise after tooth extraction. It refers to a socket following extraction that lacks epithelium, blood clot, and has an exposed bony surface, often causing intense and radiating pain. Objectives: To determine the incidence of AO among different treatment groups undergoing tooth extraction. Methods: A prospective comparative study was conducted. Patients were enrolled and allocated into treatment groups: Control, Saline Irrigation, and chlorhexidine (CHX) Rinse. Outcome measures included the incidence of AO. Statistical analysis was performed to compare outcomes between treatment groups. Results: The overall occurrence rate of dry socket was 14.22%, with the highest incidence observed in patients who received saline irrigation. Conversely, the use of chlorhexidine rinse once postoperatively resulted in the lowest incidence rate. Conclusions: It was concluded that post-operative use of chlorhexidine rinse shows a promising and favorable outcome in preventing AO among patients. However, this study does not support the justification for irrigation with saline. Further well-designed clinical trials are necessary to validate these findings.